Pengaruh Model Pembelajaran TPACK Terhadap Hasil Belajar Siswa Mata Pelajaran SKI Materi Daulah Bani Umayyah Kelas VIII MTs Muhammadiyah 25 Marubun Jaya Kabupaten Simalungun - Aninda, Nur; H, Hafsah; Syukri, Makmur (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine: 1) the learning outcomes of students before using the TPACK Learning Model of SKI subject matter Daulah Bani Umayyah of class VIII MTs Muhammadiyah 25 Marubun Jaya. 2) To determine the effect of the TPACK Learning Model on student learning outcomes in the SKI subject matter of the Daulah Bani Umayyah of class VIII MTs Muhammadiyah 25 Marubun Jaya. This type of research is Quantitative Research. With a total population of VIII grade students at MTs Muhammadiyah 25 Marubun Jaya totaling 71 people. While the sampling technique uses purposive sampling technique where the samples are class VIII-A (Experiment Class) and class VIII-B (Control Class). Data collection is done by observation and test methods. The results of the hypothesis test showed that the sig value (2-tailed) in the pre-test and post-test experiments was 0.000 <0.05 so it can be concluded that: 1) there is an effect of TPACK Learning Model on student learning outcomes in SKI subject matter Daulah Bani Umayyah class VIII MTs Muhammadiyah 25 Marubun Jaya. 2) there is a significant difference between students taught using the TPACK learning model and students taught using conventional methods.